The role of crude oil exports in increasing commercial exposure to Iraq for the period( 2004-2022) - Hammadi , Imad; Hassan, Yahya (The Gulf Economist, 2024)
The commodity of crude oil is considered one of the commodities that have a commercial weight in most countries of the world in terms of export or import, and thus its importance lies on the commercial level for both parties dealing with it, producers or consumers. Therefore, Iraq is one of those countries that relies primarily in its export of only one commodity, which is Crude oil and on top of that, the research clarified the commercial exposure aspect of Iraq during the period (2004 - 2022) by showing the quantity of oil exports compared to other commodities and the unilateral nature of the Iraqi economy through its commercial exposure to the countries of the world by exporting this commodity and importing most goods and services, and this is what indicates the increase in commercial exposure. In an unbalanced manner, it revealed a defect in dealing with the structure of Iraqi exports during the period of the research. The research reached results, the most important of which is the weakness of the country’s productive structure and the predominance of its rentier character as a result of focusing most of its attention on one sector over another sector.